The expansion of European criminal law facing the subsidiarity of criminal enforcement: alternative with Portugal's "criminal mediation for adults" - Marina Oliveira Teixeira dos Santos (Revista Brasileira de Direito Processual Penal)
This work is based on the relevance of criminal enforcement's subsidiarity and minimum criminal law's theories clashing with Europe’s criminal body of law. Therefore, initially it will be traced a framework of European criminal law's expansion, from its creation and effectiveness until the current EU's criminal jurisdiction. Afterwards, the general principles that must be observed during the analysis of EU's criminal law focusing on its subsidiarity will be studied: respectively, EU's Fundamental Rights Charter, the 2011 Commission's communication and the Manifesto on European Criminal Policy. At last, but not at all minimizing the importance of the principles studied, it shall be treated Portugal's criminal mediation for adults as an alternative to classic punitive criminal law and, due to that, means to ensure EU's criminal law subsidiarity. Hence, it will be possible to make conclusions regarding EU's expanding criminal law enforcement and solutions so that this growth does not happen without limitation – in dissonance with the ultima rationature of the criminal enforcement.